An ELISA test for the detection of antibodies to Legionella pneumophila. - Wreghitt, T G (1982)
An enzyme-linked immunosorbent assay (ELISA) test has been developed to detect antibodies to Legionella pneumophila serogroup 1. There is good correlation between indirect fluorescent antibody (IFA) and ELISA titres but ELISA is more sensitive.